A Calculation for Selection the Power of Rooftop Solar Based on the Load of the Quang Viet Factory - Van, Văn Ánh Dương; Pham, Phạm Thanh Tuân; Dinh, Đinh Xuân Lượng; Ngo, Ngô Đức Anh Quân; Tran, Trần Tiến Dũng (Journal of Technical Education Science, 2024)
Nowadays, global warming, lack of electricity, and the increase of production costs which many companies are facing. Taking advantage of available energy sources for factories and companies is an ideal choice to help them save costs and increase efficient business. In this study, the researchers have calculated, analyzed, and simulated the power of rooftop solar systems to choose optimal capacity and setup based on the power consumption of the company. From simulation and calculation results as a basis to apply to actual installation at Quang Viet factory – Long An. With the factory’s area, the number of sunshine hours, the average of radioactivation in this area, the investment costs, the loading devices used, etc., the researchers have simulated and calculated the responsiveness of the solar power system at Quang Viet factory in 53.05%, payback period is 6.2 years. From this database, it is possible to research and apply in the design and installation of rooftop solar power systems at this company.